British World Protestant Children, Young People, Education and the Missionary Movement, c.1840s–1930s - Morrison, Hugh Douglas (Studies in church history, 2019)
This article considers the evolving relationship between Protestant children, pedagogy and the missionary movement across the British world. From the 1840s, children were a central focus of missionary society philanthropy. By the time of the 1910 World Missionary Conference, missionary and denominational thinkers were consistently highlighting their strategic importance and the need for clear policy that was focused on children's education. This article traces the ways in which this emphasis developed, and the impact that it had among the children involved. It argues that the children's missionary movement was educational at heart, wherein philanthropy and pedagogy went hand in hand. In particular, over the long nineteenth century all the players consistently emphasized the importance of nurturing a ‘missionary spirit’, a notion that was primarily religious in intent but which in practice moved from pragmatic philanthropy to a more formalized emphasis on education and identity formation. The article introduces representative ways by which this was articulated, drawing on examples from a range of British world contexts in which different communities of Protestant children were engaged educationally and philanthropically in very similar ways.